Economic Lot Scheduling for Multiple Products on Parallel Identical Processors - Carreno, Jose Juan (Management Science, 1990)
This paper deals with an identical multiprocessor, multiproduct, lot-size scheduling problem under deterministic conditions. The problem is an extension of the single-processor ELSP problem. The objective is to minimize the average production and inventory costs per unit time subject to constraints of no shortages and no interference among the products. A mathematical formulation for the problem is given. A heuristic procedure, which extends the Common Cycle approach for a single processor, is suggested and computational results are reported. Upper and Lower bounds are developed and used to measure the effectiveness of the procedure.